2022
DOI: 10.3390/nu14194006
|View full text |Cite
|
Sign up to set email alerts
|

Working from Home during the COVID-19 Pandemic and Its Effects on Diet, Sedentary Lifestyle, and Stress

Abstract: Many companies switched to working from home (WFH) after the COVID-19 pandemic. This paper aimed to examine the changes in dietary behavior, body weight, sedentary lifestyle, and stress in individuals who practice WFH. A cross-sectional, web-based questionnaire was administered between March and May 2021 and included socio-demographic characteristics, anthropometric measurements, WFH arrangement, changes in diet, sedentary lifestyle, and stress status. A total of 328 individuals (260 women, 68 men), aged 31.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Another negative aspect of the forced transition to WH was that almost 40% of participants reported an increase in body weight during WH than before. This is consistent with results from other studies conducted during the lockdown imposed by the COVID-19 pandemic [ 19 , 34 , 36 , 54 , 55 ]. This finding raises concerns about the potential negative consequences for home workers, as body weight gain is associated with chronic disease risk, such as cardiometabolic disease and cancer [ 56 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Another negative aspect of the forced transition to WH was that almost 40% of participants reported an increase in body weight during WH than before. This is consistent with results from other studies conducted during the lockdown imposed by the COVID-19 pandemic [ 19 , 34 , 36 , 54 , 55 ]. This finding raises concerns about the potential negative consequences for home workers, as body weight gain is associated with chronic disease risk, such as cardiometabolic disease and cancer [ 56 ].…”
Section: Resultssupporting
confidence: 92%
“…It is interesting to note that the majority of the study participants (61.2%) were in the normal weight range for BMI on the date the questionnaire was completed, while only 7.4% were obese, and 29.4% of participants declared to be overweight, which approaches prevalence data for BMI categories in Italy [ 57 ]. Notably, an important proportion of subjects self-reported to be overweight at the compilation date, which might expose them to the risk of developing obesity during the COVID-19 pandemic [ 54 ] and to the adverse health outcomes of gaining weight.…”
Section: Resultsmentioning
confidence: 99%
“…This coincided with other dietary habits reported. In fact, a quantitative cross-sectional study from Turkey (Coşkun et al, 2022) reported weight gain in 59.1% of participants working from home during the lockdown period. Additionally, weight gain was associated with higher work hours, daily sedentary time and Non-Healthy Diet Index scores.…”
Section: Discussionmentioning
confidence: 99%
“…A Brazilian study found that individuals who were required to telework, compared with those who remained at their usual worksites, were more likely to be physically active 12 . Conversely, working from home was associated with greater sedentary time among Turkish employees 28 . Studies of Japanese workers found that teleworkers experienced large declines in active commuting—declines which were not offset by commensurate gains in noncommute active transportation 14 .…”
Section: Discussionmentioning
confidence: 99%
“…12 Conversely, working from home was associated with greater sedentary time among Turkish employees. 28 Studies of Japanese workers found that teleworkers experienced large declines in active commuting-declines which were not offset by commensurate gains in noncommute active transportation. 14 They also performed less PA during work time, relative to those who remained in the office, with the share of worktime spent teleworking inversely correlated to PA participation.…”
Section: Discussionmentioning
confidence: 99%